Hyperlactatemia and pulmonary gas exchange at rest and during exercise: lessons from patients on metformin - Philippe Haouzi; William W. Stringer; Jonathan Mccully; Bohdan M. Pichurko (European Journal of Applied Physiology, 2026)

Physiological responses to matched ramp-incremental exercise on recumbent cycle ergometer and treadmill in patients with heart failure - Rebeca Nunes Silva; Janos Porszasz; Carrie Ferguson; Patrícia Rehder-Santos; Meliza Goi Roscani; Claudio Ricardo de Oliveira; Aparecida Maria Catai; William W. Stringer; Audrey Borghi-Silva (European Journal of Applied Physiology, 2026)

Oxygen dissociation curve inflection point during incremental exercise: a trigger for the Bohr effect - Holger H. Burchert; William W. Stringer; Ranjan K. Dash (Pflügers Archiv - European Journal of Physiology, 2025)
We previously hypothesized that the inflection point of the oxygen dissociation curve (ODC) is linked to the gas exchange threshold (GET) during cardiopulmonary exercise testing. This hypothesis was supported by femoral venous blood gas data sampled during constant exercise below and above the GET, which showed that the ODC shifts rightward at the GET. What had gone unnoticed since these original observations in 1994 was that this rightward shift begins slightly earlier, precisely when the oxygen saturation crosses the ODC inflection point. To investigate this phenomenon, we analyzed the 1994 femoral venous blood gas data obtained during cardiopulmonary exercise testing using a modern validated mechanistic biochemical model of oxygen (O 2 ), carbon dioxide (CO 2 ), and proton binding to hemoglobin (Hb). We constructed the ODC for each data point, as well as the in vivo ODC—a composite curve reflecting changes in dynamic blood chemistry during exercise—to assess its alignment with the GET. The model revealed that, at the in vitro ODC inflection point (36% O 2 Hb saturation), the amounts of CO 2 bound to Hb equalized with HbNH 3 + eventually predominating. This equilibrium apparently triggered the Bohr shift, steepening the in vivo ODC to improve O 2 unloading to the tissues. Shortly afterwards, the in vivo ODC reached its inflection point, matching the measured GET. Our findings support that the GET is mechanistically linked to the in vivo ODC inflection point. These results highlight the physiological relevance of determining the ODC inflection point and its alignment with HbNH 3 + and CO 2 binding as critical factors in understanding ODC shifts during cardiopulmonary exercise testing.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Lack of effect of an in-line filter on cardiopulmonary exercise testing variables in healthy subjects - Asghar Abbasi; Khadije Ahmad; Carrie Ferguson; April Soriano; Robert Calmelat; Harry B. Rossiter; Richard Casaburi; William W. Stringer; Janos Porszasz (European Journal of Applied Physiology, 2024)

Oxygen uptake efficiency plateau: physiology and reference values - Xing-Guo Sun; James E. Hansen; William W. Stringer (European Journal of Applied Physiology, 2012)

Non-linear cardiac output dynamics during ramp-incremental cycle ergometry - William W. Stringer; Brian J. Whipp; Karlman Wasserman; Janos Prszsz; Peter Christenson; William J. French (European Journal of Applied Physiology, 2005)